Звездочки в Сатурне: семиотическая война в России и в Советском Союзе - Colombo, Duccio (Studia Rossica Posnaniensia, 2025)
Anti-war opposition in today’s Russia is often conveyed by encoded graffiti or billboards – a girl was even arrested for showing a blank piece of paper. Everybody, anyway, perfectly understands what is written on a white sheet. To understand the reason we have to look back at the late-soviet times: “Aesopian language” was then so widespread, that people used to catch allegories even where the author did not have the least intention. This can be clearly observed in the history of the Soviet spy-thriller, where in books by the most loyal of authors it is hard not to catch hidden contestant messages: the case of Vasilii Ardamatskii is emblematic. Was “Aesopian language” really a means to make such messages pass behind the eye of the censor? Or, in other words, did the struggle concern the control of the production of messages or rather that of their reception? Soviet power itself often recurred to allegories (what is now commonly called Newspeak): does it mean that the system itself carried the seeds of its own destruction? The opinion exists, on the other hand, that the situation worked in fact for the system: people did not have to believe in what they said, they just had to be taught to lie. If this is true, “Aesopian language” ultimately works for those in power. “Aesopian language” works, as a matter of fact, rather as art does: its concern is a criticism of language, therefore – of the power’s linguistic practices.